2015
DOI: 10.1038/ncomms9584
|View full text |Cite
|
Sign up to set email alerts
|

The Lin28/let-7 axis is critical for myelination in the peripheral nervous system

Abstract: MicroRNAs (miRNAs) are crucial regulators of myelination in the peripheral nervous system (PNS). However, the miRNAs species involved and the underlying mechanisms are largely unknown. We found that let-7 miRNAs are highly abundant during PNS myelination and that their levels are inversely correlated to the expression of lin28 homolog B (Lin28B), an antagonist of let-7 accumulation. Sustained expression of Lin28B and consequently reduced levels of let-7 miRNAs results in a failure of Schwann cell myelination i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 43 publications
(50 reference statements)
2
37
0
Order By: Relevance
“…To assess similarities and differences in the requirement of miRNA biogenesis pathway components Drosha, Dgcr8, and Dicer in developing SCs quantitatively and in parallel, we generated conditional SC‐specific loss‐of‐function mice ( Mus musculus ) for Dicer (Dicer cKO), Dgcr8 (Dgcr8 cKO), and Drosha (Drosha cKO) using a previously established Cre recombinase system expressed under Dhh gene regulatory sequences (Figure a) (Jaegle et al, ). As expected, the levels of Dicer, Dgcr8, and Drosha mRNAs and SN‐enriched miRNAs (Gökbuget et al, ) were strongly diminished in respective mutant mice at postnatal day (P) 1 (Figure b–e). Morphological analysis of SNs at P24 revealed numerous aberrant large bundles of unsorted axons, usually a unique feature of SC differentiation during the early stage of radial sorting, specifically in Dgcr8 cKO and Drosha cKO (Figure f–i).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…To assess similarities and differences in the requirement of miRNA biogenesis pathway components Drosha, Dgcr8, and Dicer in developing SCs quantitatively and in parallel, we generated conditional SC‐specific loss‐of‐function mice ( Mus musculus ) for Dicer (Dicer cKO), Dgcr8 (Dgcr8 cKO), and Drosha (Drosha cKO) using a previously established Cre recombinase system expressed under Dhh gene regulatory sequences (Figure a) (Jaegle et al, ). As expected, the levels of Dicer, Dgcr8, and Drosha mRNAs and SN‐enriched miRNAs (Gökbuget et al, ) were strongly diminished in respective mutant mice at postnatal day (P) 1 (Figure b–e). Morphological analysis of SNs at P24 revealed numerous aberrant large bundles of unsorted axons, usually a unique feature of SC differentiation during the early stage of radial sorting, specifically in Dgcr8 cKO and Drosha cKO (Figure f–i).…”
Section: Resultssupporting
confidence: 73%
“…The long RNA sequencing data have been deposited at the NCBI GEO database with the primary accession code GSE109075. The long RNA sequencing data for conditional Dicer mutants and controls was retrieved from the dataset available at the NCBI GEO database (GSE64562) (Gökbuget et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A). A recent study has revealed that peripheral nerve KROX20 induction is regulated by the Lin28/Let-7 axis (Gokbuget et al 2015). Lin28 is a conserved RNA-binding protein that is expressed highly in embryonic stem cells.…”
Section: Bcl2mentioning
confidence: 99%
“…Let-7 promotes expression of the myelination-driving master transcription factor Krox20 (also known as Egr2) through suppression of myelination inhibitory Notch signaling. As let-7 is also highly expressed in CNS, it remains unknown if let-7 is also responsible for CNS myelinations [80]. …”
Section: Micrornas and Extrinsic Determinants Of Axon Regenerationmentioning
confidence: 99%